Biomass Oxidation: Formyl CH Bond Activation by the Surface Lattice Oxygen of Regenerative CuO Nanoleaves1. Issue 31 (26th June 2015) - Amaniampong, Prince N.; Trinh, Quang Thang; Wang, Bo; Borgna, Armando; Yang, Yanhui; Mushrif, Samir H.
Abstract An integrated experimental and computational investigation reveals that surface lattice oxygen of copper oxide (CuO) nanoleaves activates the formyl CH bond in glucose and incorporates itself into the glucose molecule to oxidize it to gluconic acid. The reduced CuO catalyst regains its structure, morphology, and activity upon reoxidation. The activity of lattice oxygen is shown to be superior to that of the chemisorbed oxygen on the metal surface and the hydrogen abstraction ability of the catalyst is correlated with the adsorption energy. Based on the present investigation, it is suggested that surface lattice oxygen is critical for the oxidation of glucose to gluconic acid, without further breaking down the glucose molecule into smaller fragments, because of CC cleavage. Using CuO nanoleaves as catalyst, an excellent yield of gluconic acid is also obtained for the direct oxidation of cellobiose and polymeric cellulose, as biomass substrates.